PENGARUH GRATIS ONGKOS KIRIM, LIVE STREAMING DAN AFFILLIATE TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DI KABUPATEN BOGOR - Mujito Mujito; Benny Osta Nababan; Muhlis Muhlis; Wulan Kurniawati (Institut Teknologi dan Bisnis Dewantara, 2025)
This Research is a type of quantitative research, namely research that uses data in the form of number analyzed using statistic analysis. This study aims to determine the influence of free shipping, live streaming, and affiliate marketing on purchasing decisions on Shopee e-commerce in Bogor Regency. The variables of Free Shipping, Live Streaming, and Affiliate toward the purchase decision resulted in an F calculated value of 21.724 with an F table value of 2.14. Therefore, 21.724 ≥ 2.14 and the significance value of 0.000 ≤ 0.1. The coefficient of determination shows the extent of the role or contribution of the independent variables, namely Free Shipping, Live Streaming, and Affiliate, in explaining the dependent variable, Purchase Decision, at 38.6%. The remaining 61.4% is explained by other variables that were not examined in this study.